2019
DOI: 10.6007/ijarafms/v9-i1/5722
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tax Moral on Sales Tax Compliance among Jordanian SME

Abstract: The current paper examines the relation between tax moral and the sales tax compliance of SMEs. The impact of tax moral on sales tax compliance has been received a very little attention. However, to date, there has been no work on the effect of tax moral on sales tax compliance among Jordanian SMEs. This relationship was then tested based on the survey outcomes from 212 SMEs serving in Jordan. The Partial Least Squares (PLS) results revealed positive influence of tax moral on sales tax compliance. Besides exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…First, the study establishes evidence concerning sales tax compliance and, as such, helps to reduce the literature gap dedicated to sales tax compliance. For example, according to Alshira'h et al, 2019 andAlm andEl-Ganainy (2013), studies on sales tax are few and far between in relationship to sales tax diffusion as a basic revenue mechanism in the majority of governments. Indeed, no study to date has been directed towards the analysis of sales tax compliance practiced in Middle Eastern and Arab countries.…”
Section: Introductionmentioning
confidence: 99%
“…First, the study establishes evidence concerning sales tax compliance and, as such, helps to reduce the literature gap dedicated to sales tax compliance. For example, according to Alshira'h et al, 2019 andAlm andEl-Ganainy (2013), studies on sales tax are few and far between in relationship to sales tax diffusion as a basic revenue mechanism in the majority of governments. Indeed, no study to date has been directed towards the analysis of sales tax compliance practiced in Middle Eastern and Arab countries.…”
Section: Introductionmentioning
confidence: 99%
“…Alshira'h A. et al [20] found a positive relationship between the tax morality of SMEs and sales tax compliance.…”
Section: Research On the Influence Of The Size Of The Business On Tax...mentioning
confidence: 99%
“…Estimates of tax non-compliance grew from JD 1,067.4m in 2011 to JD 1,578.2m in 2015, indicating an increase of about 48%. Sales tax noncompliance represented about 71% of the total tax evasion (Jordan Economic and Social Council, 2014;Jordan Independent Economic Watch, 2014), indicating that sales tax non-compliance persists as a main problem in Jordan (Alshira 'h, et al, 2019;Malkawi and Haloush, 2008).…”
Section: Role Of Patriotism 389mentioning
confidence: 99%